2015
DOI: 10.5539/elt.v8n11p99
|View full text |Cite
|
Sign up to set email alerts
|

Teacher and Learner Views on Effective English Teaching in the Thai Context: The Case of Engineering Students

Abstract: This study aimed at investigating the characteristics of effective English teachers and students as perceived by 35 teachers and 613 students, as well as according to the surveys regarding the English-teaching problems in Thailand. The instruments included two questionnaires on the characteristics of effective teachers and students as perceived by teachers and students, based on five categories: rapport, delivery, fairness, knowledge and creditability, organization and preparation. The questionnaire responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 33 publications
3
29
1
1
Order By: Relevance
“…Additionally, the finding of this study echoes the study conducted by Mamakouc & Grigoriadou (2010) which found that the use of ICT-based project can be an effective method to improve students ICT skills. Moreover, the finding of this study is in line with the study conducted by Meksophawannagul (2015) in Thailand, where the use of PBL can improve engineering students' language skills as well as critical thinking and collaborative skills (Bas, 2008). The students' L2 spoken performance considerably increased after learning through PBL since in this study, the students are required to understand instruction, recognize relevant information in written and oral text, writing script or narratives to prepare for assignments, presentation, and project (Dooly & Masats, 2010).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Additionally, the finding of this study echoes the study conducted by Mamakouc & Grigoriadou (2010) which found that the use of ICT-based project can be an effective method to improve students ICT skills. Moreover, the finding of this study is in line with the study conducted by Meksophawannagul (2015) in Thailand, where the use of PBL can improve engineering students' language skills as well as critical thinking and collaborative skills (Bas, 2008). The students' L2 spoken performance considerably increased after learning through PBL since in this study, the students are required to understand instruction, recognize relevant information in written and oral text, writing script or narratives to prepare for assignments, presentation, and project (Dooly & Masats, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…The attainment of the project can be seen in the following figure: Extensive studies have been conducted to explore and confirm the benefits of integrating PBL to ESP and EFL contexts in the last decade. Some studies were done quantitatively (Mamakou & Grigoriadou, 2010;Meksophawannagul, 2015;Affandi & Sukyadi, 2016;Alsamani & Daif-Allah, 2016) and some were done qualitatively (Foss et al, 2008;Dooly & Masats, 2010;Nikitina, 2010;Khanh, 2015). For examples, Mamakou & Grigoriadou (2010) employed an E-project-based approach in ESP learning in Greece.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Adapted from Brosh, 1996: 133) Since Brosh's study, the vast majority of work on students' perceptions of effective teaching have employed quantitative methodologies (Al-Mahrooqi, Denman, Al-Siyabi, & Al-Maamari, 2015; Alimorad & Tajgozari, 2016;Arikan, Taşer, & Saraç-Süser, 2008;Babai Shishavan & Sadeghi, 2009;Barnes & Lock, 2013;Brown, 2009;Çelik, Arikan, & Caner, 2013;Chen, Y-J, Lin, 2009;Han, 2017;Kourieos & Evripidou, 2013;Meksophawannagul, 2015;Park & Lee, 2006). The findings of these studies demonstrate several similarities, both to each other and to early studies like Brosh (1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, it was interesting to note that 'knowledge and credibility' were not mentioned anywhere near as often as in the previously cited quantitative studies. In other words, when students were asked specifically if they thought language knowledge was important, they generally answered that it was (as in, for example, Al-Mahrooqi et al, 2015;Han, 2017;Meksophawannagul, 2015). However, when they were simply asked to describe an effective teacher in their own words, language knowledge was not mentioned as frequently.…”
Section: Literature Reviewmentioning
confidence: 99%